Direct white emissive Cl-doped graphene quantum dots-based flexible film as a single luminophore for remote tunable UV-WLEDs - Wang, Xiao-Fei (2020)
Herein we first report new chlorine-doped graphene quantum dots (Cl-GQDs) that can be used in solid-state white-light-emitting diodes (WLEDs). The Cl-GQDs with a mean size of 1.53 nm are obtained by one-step hydrothermal method using β-cyclodextrin and hydrochloric acid as the source materials. The PL emission spectra of the Cl-GQDs show an excitation-wavelength-dependent behavior in the range from 300 to 380 nm excitation. Under UV irradiation, the Cl-GQDs can direct emit white light. Given that they are worth using in light-conversion, Cl-GQDs embedded solid composite film (Cl-ESCF), based on silicon resin as host material, is successfully fabricated by solution-processing approach. The freestanding Cl-ESCF has high transparency and flexibility, excellent photostability and temperature resistance, and retains its optical properties in the solid state. In order to realize its potential, the Cl-ESCF converted remote UV-pumped WLED is demonstrated. The results verify that the Cl-GQDs can be homogeneously dispersed within solid matrix without obvious aggregation so that a uniform and defect-free natural white light can be obtained. In addition, our WLED possesses favorable white-light characters with the CIE of (0.33, 0.34), moderate CCT of 5653 K, and high CRI of 87.6, as well as good color and LED stability. This single-phase rare-earth-free white-luminescent Cl-GQDs may be not only expected to prevent the drawbacks of multicolor phosphors, thereby generating high-quality white emission, but also identified to be a green alternative for conventional emitters.